Electron Microscopic Studies of Ilmenite from the Chhatrapur Coast, Odisha, India, and Their Implications in Processing. (15th July 2014) - Rao, D. S.; Sengupta, D.
Abstract : Ilmenite from the Chhatrapur coast, Odisha, India, was studied using optical microscope, X-ray diffraction, particle size analysis, and electron microprobe to decipher their micromorphology, texture(s), and elemental composition. The micromorphological features by electron microscope indicate that weathering processes such as mechanical and chemical, affected the placer heavy mineral ilmenite. These detrital ilmenites contain TiO2 in the range of 50.25% to 55.41% and FeO 42.72% to 49.99% in addition to Al2 O3, MgO, MnO, CaO, Na2 O, Cr2 O3, NiO, ZnO, ZrO2, V2 O5, and HfO2 (0 to 0.034%). Ti/(Ti + Fe) ratio in the ilmenite varied from 0.413 to 0.5, which indicates the effect of weathering/oxidation confirming microscopic observations. All the results revealed that these ilmenite grains were derived from the gneissic/granitic, basic and high grade metamorphic rocks, belonging to the Eastern Ghats Group of the Precambrian complex of coastal Orissa.